Experimental determination of REE partition coefficients between zircon, garnet and melt: a key to understanding high-T crustal processes - Taylor, Richard; Harley, S.; Hinton, R.; Elphick, S.; Clark, Christopher; Kelly, N. (Wiley - Blackwell, 2014)
The partitioning of rare earth elements (REE) between zircon, garnet and silicate melt was determined using synthetic compositions designed to represent partial melts formed in the lower crust during anatexis. The experiments, performed using internally heated gas pressure vessels at 7 kbar and 900–1000 °C, represent equilibrium partitioning of the middle to heavy REE between zircon and garnet during high-grade metamorphism in the mid to lower crust. The DREE (zircon/garnet) values show a clear partitioning signature close to unity from Gd to Lu. Because the light REE have low concentrations in both minerals, values are calculated from strain modelling of the middle to heavy REE experimental data; these results show that zircon is favoured over garnet by up to two orders of magnitude. The resulting general concave-up shape to the partitioning pattern across the REE reflects the preferential incorporation of middle REE into garnet, with DGd (zircon/garnet) ranging from 0.7 to 1.1, DHo (zircon/garnet) from 0.4 to 0.7 and DLu (zircon/garnet) from 0.6 to 1.3. There is no significant temperature dependence in the zircon–garnet REE partitioning at 7 kbar and 900–1000 °C, suggesting that these values can be applied to the interpretation of zircon–garnet equilibrium and timing relationships in the ultrahigh-T metamorphism of low-Ca pelitic and aluminous granulites.